Dietary Intake and Pregnancy Characteristics on Maternal Anemia Status - Harna Harna; Mertien Sa’pang; Andi Muh Asrul Irawan (JURNAL INFO KESEHATAN, 2025)
Anemia during pregnancy remains a significant global health concern, affecting a substantial portion of the worldwide population. The prevalence of anemia is particularly high among pregnant women, especially in developing countries like Indonesia. Anemia during pregnancy can lead to severe complications for both mother and fetus, including increased mortality risk, premature birth, low birth weight, and cognitive impairment. Purpose: This study aimed to identify factors contributing to anemia, specifically examining food intake and pregnancy characteristics. A cross-sectional study was conducted from June to September 2023 at Parung Panjang Health Center, Bogor Regency, involving 135 pregnant women. Data collection included hemoglobin measurements using an easy touch device and nutritional intake assessment through SQ-FFQ interviews. Analysis was performed using SPSS version 23 with chi-square testing. The study revealed significant correlations between parity, intake of calcium, and vitamin C with anemia status (p<0.05). Most participants were in their third trimester, predominantly unemployed, and had low education levels. There was no significant association between nutrition status, age, family income and infection story with anemia status (p>0.05). While the majority of women had adequate iron intake, no significant association was found between iron intake and anemia status (p>0.05). The study identified parity, intake of calcium, and vitamin C as significant factors associated with anemia in pregnant women. These findings emphasize the importance of comprehensive nutritional support and monitoring during pregnancy, particularly focusing on adequate micronutrient intake and considering parity status in anemia prevention strategies.